An Active Flow Control over the Ship Deck for Helicopter Shipboard Operations - Yi Ye; Renliang Chen; Honglei Ji (Aerospace, 2024)
This paper presents an active flow control of ship airwake over the deck to improve the safety of helicopter shipboard operations in various angles of wind over deck (WOD). Firstly, an integrated flight dynamics method coupled with ship airwake was developed to analyze the effect of ship airwake on the helicopter at various angles of WOD. Then, an active flow control strategy in various angles of WOD was investigated with the analysis of airwake distribution and the impact on helicopter trim flight. Finally, the effects of active blowing on airwake distribution, flight control inputs, control margins, and helicopter attitudes in trim were analyzed. The results indicate that the variation of the angles of WOD has a significant impact on flight controls and helicopter attitudes for helicopter hovering relative to ship motion. The nonuniformity of ship airwake can be effectively alleviated by applying active flow control. The variations of flight control inputs and helicopter attitude angles at trim states are reduced, which increases the control margins and contributes to enhancing the safety of helicopter shipboard operations.